A Critical Review of Sthavara Visha ‘Vatsanabha’: A Cardiotoxic Poison. - Rachna; Tomar, Brijendra Singh; Chawla, Satbir Kumar; Gusain, Tanvi (International Research Journal of Ayurveda & Yoga, 2023)
Herbal Medicines has been extensively used in India and other country for centuries. It is a common misconception among the public that Ayurvedic medicines are safe and devoid of adverse reaction. According to Toxicological text, some plants possess cardio toxic effects. Vatsanabha is a Sthavara visha which possesses anti-inflammatory & analgesic activities, and is capable of inducing severe arrhythmia and neurotoxicity. Cardio toxic effects of Vatsanabha are cause due to overdose of formulation or without purification of Vatsanabha. Fatality of Vatsanabha dose can happen on account of accidental ingestion or consumption of herbal decoction made from the aconite roots. Roots are used as diuretic, anti-periodic, anodyne, antidiabetic and antipyretic in very small doses. Aconite, in the form of tincture when applied locally can acts as a peripheral stimulant to sensory nerves producing tingling sensation followed by depression and numbness. If taken internally it stimulates the vagus nerve center and slows the heart origin. To clarify its potential risk following action, toxicological characteristics of Vatsanabha are reviewed along with its possible mode of action.